Analisis Manajemen Kompensasi - Sunaryanta, Fransiscus Xaverius (Public Administration, Faculty of Politics and Social Science, Universitas Jenderal Soedirman, Indonesia, 2023)
One of the goals of compensation is to provide rewards or rewards that are fair from both the organization's and employee's perspectives. This study aims to describe the causes of the problem of providing additional employee income for civil servants in the Pemalang Regency Government environment which is not achieved in terms of compensation management theory. In the context of public administration, this research is an effort to discuss compensation for Indonesian public employees, which often becomes controversial in reforming public personnel administration, especially in relation to the implementation of additional employee income. This study used descriptive qualitative method. In this research used primary data and secondary data. Data collection techniques were carried out by triangulation through in-depth interviews and documentation. Technical data analysis is carried out through three simultaneous activity streams, namely: data reduction, data presentation and drawing conclusions. The results of the study concluded that because the Pemalang Regency Government had not implemented the four phases of compensation management in a comprehensive manner, namely: First, Position Identification. Second, internal fairness weighting. Third, external fairness weighting. Fourth, internal and external fairness weighting alignment in determining the amount of additional employee income resulting in compensation goals in creating fair rewards or rewards not being achieved. Keywords: Compensation Management, Additional Employee Income, Internal Justice, External Justice.